Sinergi Media Sosial dan E-commerce: Resep Sukses Memasarkan Produk Olahan Pertanian - Putra, Reinaldo Dede; Marumpe, Dody Pratama; Aldy, Aldy; Visto, Yohanes; Fathoni, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Mekar Jaya Hamlet, located in Antibar Village, Mempawah Regency, West Kalimantan, Mekar Jaya Hamlet, Antibar Village, Mempawah Regency, West Kalimantan, has great potential as one of the largest pineapple producers in Indonesia, but has not been optimally utilized. This service aims to increase community income through diversification of pineapple products into value-added MSME products, such as pineapple jelly candy. The method used is education and training, with PKK women as facilitators in delivering materials to farmers. The training included how to process pineapple into jelly candy and the utilization of social media (Shopee, Facebook, Instagram) for product marketing. The results of this service are the creation of market-ready pineapple jelly candy MSME products, along with the creation of social media accounts for promotion. Some marketing content was also successfully developed to introduce the product to a wider market. In conclusion, this program increases the added value of pineapple as a local product and provides education on the use of digital technology for marketing, so it is expected to improve the welfare of the local community. succeeded in increasing the added value of pineapple as a local MSME product and providing education to the community in utilizing digital technology for marketing, so that it is expected to improve the economic welfare of the local community.